APLIKASI SISTEM PENYEDIAAN AIR BERSIH BERBASIS MASYARAKAT DI PULAU PANDANGAN, KABUPATEN PANGKAJENE, SULAWESI SELATAN - Herlambang, Arie (Jurnal Air Indonesia, 2016)
Pangkajene archipelago, is archipelago comprising 117 islands scattered in the West Coast District Pangkajene. The islands were inhabited by populations ranging from 10 to 250 heads of families. Most of the population livelihood as a fisherman. To support the daily basic needs are still supplied from the mainland, including the need for clean water. Community water needs during this time a lot depends on rain water that collected or from shallow groundwater. In line with population growth, water demand increases, so frequent water shortages, especially during the dry season. Sea water treatment technology with reverse osmosis systems is an alternative to the settlement of water shortage on the island, but because the number of islands many, it will be difficult to meet the needs of water in a short time. Therefore chosen the middle position of the three islands (Cakdi Saroppe Island, Island and Island Sanane view) as a distribution center. Installed capacity for each of the islands is 10 m3/day, which can serve to the needs of drinking water a thousand people. Water treatment technology with reverse osmosis pretreatment consist of the form of multi-media filter consisting of silica sand, zeolite, and activated carbon, followed by cartride filter and a reverse osmosis membrane. Construction of the water treatment unit involves people since it began surveying best location, construction, training and initial operation. Water that has been processed can drink for everyday purposes, therefore, to support the operations of the water is sold to the public for replacement of operational money. The biggest cost needed to produce water is the cost of fuel. By managing the sale of water expected operating costs can be met and comunity get drinking water at an affordable price.Keyword : dringking water, reverse osmosis, society engangement.